PASSION VS. PARENTAL PRESSURE: WHAT DRIVES STUDENTS TO CHOOSE MEDICINE IN GOVERNMENT MEDICAL COLLEGES OF AZAD JAMMU & KASHMIR (AJK) PAKISTAN? - Rashad Mahmood Mirza (International Journal of Literature and Language Studies, 2026)
Objective: To identify the factors that influence students in government sector medical colleges of Azad Jammu and Kashmir, Pakistan, when choosing between medicine as a career. Study Design: A cross-sectional study was conducted. Setting: The research was carried out in government sector medical colleges across (AJK), Pakistan. Period: Data collection took place from 1st March 2025 to September 2025. Methods: A total of 260 students were recruited using non-probability convenience sampling. A structured questionnaire was used to gather information on socio-demographics and to assess motivational factors—such as personal passion and parental pressure—using a five-point Likert scale. The data were analyzed using SPSS version 26.0, with descriptive statistics applied to categorical variables and chi-square tests used to compare responses across gender. Results: Out of 260 participants, 90 were male and 170 were female, with 167 enrolled in MBBS and 93 in BDS programs. Personal passion was the leading factor influencing career choice, reported by 81.5% of students, followed by prestige and social status at 55.7% and financial stability at 51.9%. External inspiration was noted by 47% of participants, while parental pressure was the least reported factor at just 23%. No significant gender differences were observed in any of these motivational factors. When asked about alternative careers, most students named Information Technology, Business Management, or Engineering as their next choice if not medicine. Conclusion: Students choose medical or dental careers not only out of personal interest but also due to social status, financial independence, and external inspiration. Both male and female students share largely similar aspirations in this regard.